Laju transmisi penyakit ice-ice pada rumput laut Kappaphycus alvarezii berdasarkan jarak tanam dengan metode longline - Aris, Muhammad; Ibrahim, Tamrin Ali (e-Journal BUDIDAYA PERAIRAN, 2020)
Kappaphycus alvarezii seaweed is one of the main commodities of aquaculture which is economically important and has been cultivated commercially. In the Kappaphycus alvarezii seaweed cultivation system, the attack of ice-ice is a major obstacle because it can harm the cultivation business. The spread of the disease can occur vertically and horizontally. This study aimed to observe the horizontal transmission rate of ice-ice disease in cultivation activities of K. alvarezii in Maba Waters, East Halmahera Regency. The results showed that the attack of ice-ice caused a decrease in growth and experienced death. The presence of this disease in seaweed cultivation can result in a decrease in seaweed production. This is a major problem faced by K. alvarezii seaweed cultivation managers and requires serious handling with proper management